AH Peptide-Mediated Formation of Charged Planar Lipid Bilayers - Zan, Goh Haw (2016)
Planar lipid bilayers on solid supports provide a controllable platform to mimic biological membranes. Adsorption and spontaneous rupture of vesicles is the most common method to form planar bilayers. While many substrates support vesicle adsorption, vesicles rupture spontaneously on only a few materials. In order to form planar bilayers on materials intractable to conventional vesicle fusion, an amphipathic, α-helical (AH) peptide has been identified that can rupture adsorbed vesicles and form planar bilayers on previously intractable materials. Most studies using AH peptide have employed zwitterionic lipid compositions only, and the range of suitable lipid compositions remains to be elucidated. Herein, using quartz crystal microbalance-dissipation and ellipsometry, we investigated the effects of membrane surface charge on AH peptide-mediated bilayer formation via the rupture of surface-adsorbed vesicles on titanium oxide. Our findings demonstrate that AH peptide can promote the formation of positively and negatively charged bilayers. Importantly, the kinetics of vesicle rupture by AH peptide are strongly influenced by the membrane surface charge. Although the titanium oxide surface is negatively charged, the formation of negatively charged bilayers was quickest among the tested lipid compositions. Taken together, the experimental data supports that the effects of membrane surface charge on the rupture kinetics are related to variations in the extent of vesicle destabilization prior to vesicle rupture. Given the wide range of lipid compositions amenable to AH peptide-mediated vesicle rupture, this work further suggests that AH peptide is largely unique among membrane-active peptides, thereby substantiating its position as a promising broad-spectrum antiviral agent.